Tendencias De Contaminantes En Área Metropolitana De Monterrey Para El Formulamiento De Estrategia De Mitigación - Bazurdo Montes, Juan Manuel (Universidad Antonio Nariño, 2023)
The Monterrey Metropolitan Area (AMM) is the nucleus of industrial activity in the State of Nuevo León in Mexico. The population has gone down quickly. like industry, which has negatively affected air quality. At the beginning of the 90's, the application of these measures began through the installation of measurement stations that would allow an overview of the situation of the AMM to be obtained. As it expanded economically, more measurement stations were installed. The purpose of this paper is to present the evolution of pollutants: sulfur dioxide (SO2), nitrogen dioxide (NO2), carbon monoxide (CO) and particulate matter (PM10 and PM2.5). To provide improvement strategies in the city.